2002
DOI: 10.1023/a:1014484821460
|View full text |Cite
|
Sign up to set email alerts
|

A Phase II Trial of Pyrazine Diazohydroxide in Patients with Disseminated Malignant Melanoma and no Prior Chemotherapy – Southwest Oncology Group Study

Abstract: Malignant melanoma is rapidly increasing in the United States. Metastatic disease responds poorly to currently available chemotherapy. Pyrazine diazohydroxide (PZDH) is a new agent inhibiting DNA synthesis that is active in mouse tumor models and human xenografts and lacks cross resistance with multiple standard agents. In this phase II trial, patients with no prior chemotherapy or immunotherapy for metastatic disease and performance status (SWOG) of 0-1, were treated with pyrazine diazohydroxide at a dose of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 4 publications
(5 reference statements)
0
5
0
Order By: Relevance
“…Interestingly, in comparison to the other complexes, 2 exhibits some degree of selectivity with a 2-fold stronger growth inhibition effect on A2780 cancer cells compared to noncancerous HEK293 cells. Over time the complexes are likely to release highly cytotoxic diazotates under physiological conditions. It has been previously shown that diazotates interact with a number of different biomolecular targets. ,, Because these targets are not cancer-cell-specific, the similar cytotoxicities observed in the tumorigenic and nontumorigenic cell lines studied here are not unexpected. In addition, the palladium fragment is also likely to exert a cytotoxic effect, and previous palladium­(II) complexes have been shown to bind to a number of different targets including DNA, also rationalizing the lack of cancer cell specificity.…”
mentioning
confidence: 61%
See 2 more Smart Citations
“…Interestingly, in comparison to the other complexes, 2 exhibits some degree of selectivity with a 2-fold stronger growth inhibition effect on A2780 cancer cells compared to noncancerous HEK293 cells. Over time the complexes are likely to release highly cytotoxic diazotates under physiological conditions. It has been previously shown that diazotates interact with a number of different biomolecular targets. ,, Because these targets are not cancer-cell-specific, the similar cytotoxicities observed in the tumorigenic and nontumorigenic cell lines studied here are not unexpected. In addition, the palladium fragment is also likely to exert a cytotoxic effect, and previous palladium­(II) complexes have been shown to bind to a number of different targets including DNA, also rationalizing the lack of cancer cell specificity.…”
mentioning
confidence: 61%
“…They are key intermediates in Gomberg–Bachmann aromatic C–H activation , and other organic processes that involve diazonium salts. Diazotates are important from the biological perspective because they are involved in nitric oxide-induced DNA damage and are believed to be one of the reactive intermediates that form during the decomposition of N -nitrosamines . Earlier studies showed that the relatively stable sodium pyrazine-2-diazotate (half-life 44 min at pH 7) exhibited substantial activity against a number of cancers. The low stability as well as limited number of readily available diazotates narrows the utility of this important class of compounds.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Although PZA is the first-line antituberculotic drug, it was found that this molecule has exhibited other interesting biological activities such as antifungal, antibacterial, antiviral and antineoplastic effects [15,16,17,18,19,20].…”
Section: Introductionmentioning
confidence: 99%
“…PZA and its derivatives have also many other useful applications, as they show antiviral, antifungal, antibacterial and as well as antineoplastic activities [14,15,16,17,18,19,20]. Several pyrazine derivatives were also found to inhibit photosynthetic electron transport (PET) in plant chloroplasts [21,22,23].…”
Section: Introductionmentioning
confidence: 99%